If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -1 = 9 + -3p Reorder the terms: -1 + 2p = 9 + -3p Solving -1 + 2p = 9 + -3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3p' to each side of the equation. -1 + 2p + 3p = 9 + -3p + 3p Combine like terms: 2p + 3p = 5p -1 + 5p = 9 + -3p + 3p Combine like terms: -3p + 3p = 0 -1 + 5p = 9 + 0 -1 + 5p = 9 Add '1' to each side of the equation. -1 + 1 + 5p = 9 + 1 Combine like terms: -1 + 1 = 0 0 + 5p = 9 + 1 5p = 9 + 1 Combine like terms: 9 + 1 = 10 5p = 10 Divide each side by '5'. p = 2 Simplifying p = 2
| 2(-6x-5)=-46 | | 218-4x=32x+18 | | 4x-9=9-x | | 9-10x=45-24x | | 3(4)+3(4x-4)+2(4)+2(x-1)=7(x-1)+7(4x-4) | | -38-9x=9x+16 | | 12x+7=8x+31 | | 6x+13=-35-10x | | -8-6x+x=-13 | | -2(-6x+3)=30 | | 166-6x=6x+10 | | 3+3x=-60+4x | | -6(7x+3)=-60 | | 11-4c=7-8c | | -17-4x=10-7x | | 2n-3=7 | | -4(8+2x)=-120 | | 4f+17=17+4f | | 95-3x=9x+23 | | 4x+2=-6-6x | | 6(2+2x)=-72 | | 4x+8=98-5x | | -6y+5x=6 | | -2(5+2x)=-42 | | -117=3x+7x+3 | | 5+7x=23+x | | 7(-5x+10)=-35 | | -13=3x+x-7 | | 3(4)+3(4x-4)+2(4)+2(4x-4)=7(x-1)+7(4x-4) | | 7(2-x)=-49 | | -4(4x-1)=-44 | | -2x+9=-15+4x |